PATHOGENICITY AND IMMUNOGENICITY OF PARACOCCIDIOIDES-BRASILIENSIS ISOLATES IN THE HUMAN-DISEASE AND IN AN EXPERIMENTAL MURINE MODEL - Singervermes, L. M.; Burger, E.; Calich, VLG; Modestoxavier, L. H.; Sakamoto, T. N.; Sugizaki, M. F.; Meira, D. A.; Mendes, R. P. (Blackwell Science, 1994)
The pathogenicity and immunogenicity of six recently isolated Paracoccidioides brasiliensis samples derived from patients presenting distinct and well defined clinical forms of paracoccidioidomycosis (PCM) were compared as to their virulence, tropism to different organs and ability to induce specific cellular and humoral immune response in susceptible (B10.A) inbred mice. Isolates Pb44 and Pb47 were obtained from acute cases, Pb50 from a chronic severe form, Pb45 from a chronic moderate case and both Pb56 and Pb57 from chronic mild forms of PCM. Pathogenicity and tropism of each fungal sample were evaluated by LD50% estimation, examination of gross lesions on various organs at 2, 4, 12 and 16 weeks post-infection, and by colony-forming unit (CFU) counts in the lungs at week 16 post-infection of mice. Fungal tropism in human PCM and in B10.A mice was always dissociated. A well defined relationship between virulence of the fungal sample and the clinical findings of the correspondent patient was not evident, although a tendency to higher LD50% and less intense paracoccidioidic lesions was observed in mice infected with Pb56 and Pb57. The specific DTH response patterns varied according to the infectant sample, but positive DTH reactions at the beginning of the infection and a tendency to anergy or low DTH responses at week 12 and/or week 16 post-infection were always observed. A correspondence between the DTH response in humans and in mice was noticeable only when the isolates from the most benign cases (Pb56 and Pb57) were considered. The specific antibody patterns in mice and in the correspondent patients were also not analogous. Collectively, these results indicate that an association between the fungal pathogenicity and immunogenicity in the human disease and in susceptible mice was discernible only when isolates obtained from very mild cases (Pb56 and Pb57) were considered.
Keywords: PARACOCCIDIOIDOMYCOSIS; ISOGENIC MURINE MODEL; FUNGAL VIRULENCE; DTH REACTIONS